2009
DOI: 10.1038/nrgastro.2009.165
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation after radioembolization in a patient with unresectable HCC

Abstract: Background-A 58-year-old white man who was being followed by his hepatologist for nonalcoholic steatohepatitis-related liver cirrhosis and portal hypertension and who had been found to have a biopsy-proven hepatocellular carcinoma (HCC) on routine screening, self-referred to our center for a second opinion on the management of his HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For such reasons, hepatic resection after RE is very limited to anecdotal cases [5][6][7][8][9]. Recently it has been reported a case of liver metastases who underwent hepatic resection after downstaging with RE [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such reasons, hepatic resection after RE is very limited to anecdotal cases [5][6][7][8][9]. Recently it has been reported a case of liver metastases who underwent hepatic resection after downstaging with RE [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is usually offered to patients with advanced liver cancers who are not otherwise candidates for local ablation, surgical resection, liver transplantation (LT) or have failed other previous treatment as TACE or chemotherapy. For such reasons, surgical experience after RE is very limited to anecdotal cases or small series [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Y90-SIRT has led to the discovery of several novel concepts which may help patients who are undergoing potentially curative resection ( 49 50 ). One of them is the controversial downstaging as a bridge to liver resection or transplantation in selected candidates ( 16 51 52 53 54 ). Kulik et al ( 55 ) reported that following Y90-SIRT, 19 of 34 (56%) patients were successfully downstaged from UNOS T3 to T2, and of these patients, eight (23%) underwent liver transplantation.…”
Section: Y90-sirt Outcomesmentioning
confidence: 99%
“…[1,2] In ltration into adjacent tissues and metastasis to distant organs are the causes of death in the majority of HCC patients. [3,4] Thus far, the detailed molecular mechanisms underlying the initiation and progression of tumor metastasis remain far from fully understood. As a result, medical prevention and treatment of HCC is disappointing.…”
Section: Introductionmentioning
confidence: 99%